Analysis of a virtual state using the complex scaling method - M, Odsuren; G, Khuukhenkhuu; S, Davaa; K, Kato (Scientific transaction of the National University of Mongolia. Physics, 2022)
We investigate the virtual state using a simple schematic two-body model which simulates 8Be+n system and the complex scaling method. PACS numbers: 27.20.+n 6 A 19, 21.60.Gx, 24.30.Gd, 25.20.Lj